Hepatitis B reactivation in patients with chronic hepatitis C undergoing anti‐viral therapy with an interferon‐free regimen. Issue 8 (16th February 2017) - Londoño, M.‐C.; Lens, S.; Mariño, Z.; Bonacci, M.; Ariza, X.; Broquetas, T.; Pla, A.; Bartres, C.; Adriani, M. V.; Rodríguez‐Tajes, S.; Costa, J.; Carrión, J. A.; et al.
Summary: Background: A few cases of hepatitis B virus (HBV) reactivation during anti‐viral therapy against hepatitis C (HCV) have been reported. However, the information regarding the real impact of this phenomenon is scarce. Aim: To evaluate the risk of HBV reactivation during anti‐viral therapy against HCV with an interferon‐free regimen with direct‐acting anti‐virals (DAAs). Methods: Observational and prospective study of 352 patients receiving DAAs therapy between September 2015 and May 2016. HBV‐DNA and ALT levels were monitored at baseline, at week 4 of anti‐viral therapy, at end of treatment and 12 weeks after treatment discontinuation in patients with HBV surface antigen (HBsAg) positive or HBV core antibody (anti‐HBc) positive before starting anti‐viral therapy. Results: Ten (2.8%) and 64 (18%) patients were HBsAg and anti‐HBc positive at baseline, respectively. Five (50%) of 10 HBsAg positive and one (1.6%) of 64 anti‐HBc positive patients presented HBV virological reactivation (>1log increase in HBV‐DNA levels). None of these patients presented clinical reactivation (increase in ALT levels). Conclusions: HBV virological reactivation is frequent in HBsAg+ patients receiving anti‐viral therapy against HCV. However, HBV‐DNA elevations were modest (<20 000 IU/mL) and without clinical impact (no ALT elevation). Abstract : Linked Content This article is linked to Londoño et al, Huang et al, Chen, Wang and Kao, Hsu et al papers. To view these articles visithttps://doi.org/10.1111/apt.14104, https://doi.org/10.1111/apt.14080, https://doi.org/10.1111/apt.14051, https://doi.org/10.1111/apt.14116 andhttps://doi.org/10.1111/apt.14127 .